Slovenian Friars Minor’s efforts for dialogue with muslims - Osredkar, Mari Jože (Array, 2021)
The point of departure of the article are the Catholic theological foundations for interreligious dialogue written at the Second Vatican Council. The documents of the last church Council encourage Pope Francis to imitate the Poor from Assisi, whose name he chose when he was elected Pope. On the occasion of his visit to Abu Dhabi, for the first time after the conquests of Islam, he celebrated Holy Mass on the Arabian Peninsula and assured Muslim leaders that he was coming to visit them as a brother. He signed a document on world fraternity with the great Iman of the Egyptian Islamic University, in which they wrote that everyone, Christians and Muslims, is created as a child of God. They invite people to respect each other and work for peace despite their differences. The initiator of the dialogue between Friars Minor and the Muslims is Francis of Assisi, who 800 years ago held a peaceful meeting with Sultan Al-Kamil in Damietta, Egypt, in an atmosphere of respect and mutual acceptance. The purpose of our work is however to introduce the actual efforts of the Slovenian Franciscans for Dialogue with Muslims.